Atributos da qualidade do solo sob cultivo de bananeira em sistema de transição agroecológico - Godoy, Sinnara Gomes de (2009)
The scope of the sustainability of agricultural ecosystems is the maintenance and / or improving soil quality, which can be measured by means of chemical, physical and microbiological. The aim of this study was to evaluate the physical, chemical and microbiological, in a biological approach in banana cultivation under irrigation in the transitional agro-ecological system in reference to a system in equilibrium. The experiment was conducted between winter 2008 and summer 2009 in two areas under banana cultivation with and without the application of chemical inputs associated with organic inputs in the municipality of Itapuranga - GO. Samples were collected at a depth 00-10 cm in September 2008 and March 2009 in the region of banana roots. The attributes were: texture, pH in CaCl2, macronutrients (P, K, Ca and Mg) and organic matter content of soil, density, porosity, microbial biomass, basal respiration, metabolic quotient and total enzymatic activity. The classical statistics was applied to identify the effect of chemical inputs in different areas under evaluation. The soil has chemical, physical and microbiological environment varied as a function of agroecological transition in banana cultivation in the area where there was an application of chemical inputs does not negatively impacted the quality of soil, since the area in which there was only the application of organic inputs still requires adequate system of banana cultivation for achieving sustainability.